3D printing adhesive, preparation method and application thereof

By using 3D printed materials prepared with UV glue and polyamide wax, combined with a specific dispersion process, the problem of poor conformal properties of high elastic resins is solved, and the effects of high thixotropy, high elasticity and precision printing are achieved.

CN119735944APending Publication Date: 2025-04-01ENOVATE3D (HANGZHOU) TECH DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411917893.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing high elastic resin has poor conformal properties and is difficult to meet the requirements of precision printing in specific areas.

Method used

UV glue and polyamide wax are used as raw materials, and 3D printed materials with a thixotropy index of 2 to 2.6, Young's modulus ≤10MPa, and elongation of breaking is prepared through a specific dispersion process, including fluid shear and mechanical dispersion.

Benefits of technology

It realizes the improvement of thixotropy while retaining the high elasticity characteristics of the resin, meets the requirements of high aspect ratio, low line width, and stable printing, reduces the risk of plugging the needle, improves the uniformity of the line, and is suitable for precision printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735944A_ABST
    Figure CN119735944A_ABST
Patent Text Reader

Abstract

The present invention provides a 3D printing rubber, a preparation method and application thereof. The raw materials of the 3D printing rubber include UV glue and polyamide wax, the thixotropic index of the 3D printing rubber is 2 to 2.6, the Young's modulus is ≤10MPa, and the elongation at break is 150 to 350%; the printing line width of the 3D printing rubber is ≤500μm, the line width fluctuation of 30 lines printed in 80cm is ≤±5%, and the printing aspect ratio is 0.1 to 0.13. The present invention improves the conformal performance of the 3D printing rubber by adding polyamide wax as a thixotropic additive, and controls the thixotropic index, printing line width fluctuation and other parameters within a specific range to meet the requirements of precision printing in a specific area, and can improve the thixotropy while retaining the high elastic characteristics of the resin, meet the requirements of aspect ratio, low line width and stable printing, and has a small risk of needle blocking when used for 3D printing, good line uniformity, and is suitable for precision printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of resin technology, and in particular to a 3D printing adhesive, a preparation method and application thereof. Background Art

[0002] Existing display products, such as some flexible screens and folding screens, require the use of highly elastic resins for bonding and packaging. Existing highly elastic resins generally have poor conformal properties and are difficult to meet the requirements of precision printing in specific areas. Generally, the conformal properties of the resin are improved by adding thixotropic additives. Thixotropic additives are mainly divided into inorganic thixotropic additives and organic thixotropic additives. Common ones include fumed silica, organic bentonite, polyamide wax, polyethylene wax, hydrogenated castor oil, etc. Flexible polymer substrate materials are the materials chosen by most flexible display manufacturers. Compared with ultra-thin glass and metal foil, they have the advantages of better flexibility, lighter weight and greater impact resistance. However, the melting point of flexible substrates is generally low, and slightly higher temperatures may cause distortion and deformation problems. Therefore, for the sake of temperature resistance, light-curing UV resin materials suitable for temperature-sensitive substrates and components become the preferred choice.

[0003] Chinese patent CN 115537167 A discloses a UV-curable cofferdam glue and its preparation method, wherein a rheological additive is added to an acrylic resin to improve thixotropy, wherein the preferred rheological additive is silica, and the obtained cofferdam glue has high thixotropy, can be quickly and deeply cured under UV irradiation, and can greatly improve production efficiency and output. However, it uses an inorganic thixotropic additive, fumed silica, to improve thixotropy. After silica enters the system, it will change the overall mechanical properties of the system, increase the hardness, increase the elastic modulus, and decrease the elongation at break, making it impossible for the resin to have both high thixotropy and high elasticity. The introduction of the thixotropic additive may also cause uneven dispersion of the resin due to the formation of aggregates or residual unactivated thixotropic additives due to its insufficient activation. During use, especially when used as a material for 3D printing, there is a risk of needle blocking, which affects the uniformity of the printing line type, resulting in failure to meet the actual application requirements of precision printing. Summary of the invention

[0004] The main purpose of the present invention is to provide a 3D printing rubber material, a preparation method and application thereof, so as to solve the problem in the prior art that high elastic resin has poor shape retention and is difficult to meet the requirements of precision printing in specific areas.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a 3D printing adhesive is provided, wherein the raw materials include UV adhesive and polyamide wax, the thixotropic index of the 3D printing adhesive is 2 to 2.6, the Young's modulus is ≤10MPa, and the elongation at break is 150 to 350%; the printing line width of the 3D printing adhesive is ≤500μm, the line width fluctuation of 30 lines printed in 80cm is ≤±5%, and the printing aspect ratio is 0.1 to 0.13.

[0006] Furthermore, the UV glue comprises a main resin, and the main resin comprises one or more of polyurethane acrylate, polyester acrylate, polyether acrylate, silicone modified acrylate and acrylic resin; and / or the particle size D of the polyamide wax is max ≤20μm.

[0007] Furthermore, the UV glue is one or more of Henkel Loctite's 3318LV, 3410, Permabond's UV 639, Shin-Etsu's KUV-3433-UV; and / or the polyamide wax is one or more of Arkema's LV, SL, SLX, SLT, Super, Optima, Core Chemical's D680, and Metson's MT Plus.

[0008] Furthermore, the weight ratio of UV glue to polyamide wax is 100:(1-2).

[0009] According to another aspect of the present invention, a preparation method of the above-mentioned 3D printing glue of the present invention is provided, comprising the following steps: step S1, mixing UV glue and polyamide wax, performing first fluid shearing, and obtaining a pre-dispersed material; step S2, performing first mechanical dispersion and second fluid shearing on the pre-dispersed material in sequence to obtain a pre-treated material; step S3, performing a second mechanical dispersion on the pre-treated material at 60-80°C, the second mechanical dispersion comprising 2-3 dispersion cycles, and performing at least one third fluid shearing between each dispersion cycle to obtain an activated material; step S4, filtering the activated material and performing a fourth fluid shearing, then performing a third mechanical dispersion at 60-80°C, and finally performing a fifth fluid shearing and centrifugation in sequence to obtain a 3D printing glue.

[0010] Furthermore, in step S1, the shearing temperature of the first fluid is 20-30°C, the rotation speed is 1500-2000 rpm, and the time is 5-20 min.

[0011] Furthermore, in step S2, the temperature of the first mechanical dispersion is 30-50°C, the rotation speed is 1000-3000rpm, and the time is 0.5-3h; and / or the temperature of the second fluid shear is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min.

[0012] Furthermore, in step S3, the temperature of the second mechanical dispersion is 60-80°C, the rotation speed is 1000-3000 rpm, and the total time is 0.5-1h; and / or the time of a single dispersion cycle is 15-25min; and / or the temperature of the third fluid shear is 20-30°C, the rotation speed is 1500-2000 rpm, and the time is 5-20min.

[0013] Furthermore, in step S4, the temperature of the fourth fluid shearing is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min; and / or the temperature of the third mechanical dispersion is 60-80°C, the rotation speed is 1000-3000rpm, and the time is 10-30min; and / or the temperature of the fifth fluid shearing is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min.

[0014] Further, in step S4, filtering is performed using a filter screen having a pore size of 5 to 50 μm; and / or the centrifugal temperature is 20 to 30°C, the rotation speed is 2000 to 4000 rpm, and the time is 5 to 10 min; and / or after the fifth fluid shearing, step S4 also includes the following steps: rolling the material, shearing it with the sixth fluid, and centrifuging it in sequence to obtain a 3D printing rubber material; wherein the sixth fluid shearing temperature is 20 to 30°C, the rotation speed is 1500 to 2000 rpm, and the time is 5 to 20 min.

[0015] According to another aspect of the present invention, there is provided an application of the above-mentioned 3D printing adhesive of the present invention in precise control of printed circuits in flexible display, precision optics and electronic circuit protection.

[0016] By applying the technical solution of the present invention, polyamide wax is added as a thixotropic additive to improve the conformal properties of 3D printing rubber, and parameters such as the thixotropic index and printing line width fluctuation are controlled within a specific range to meet the requirements of precision printing in specific areas. The thixotropy can be improved while retaining the high elastic characteristics of the resin to meet the requirements of high aspect ratio, low line width and stable printing. When used for 3D printing, the risk of needle blocking of the rubber is small, the line shape uniformity is good, and it is suitable for precision printing. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 Shown is a printing circuit diagram according to Embodiment 1 of the present invention;

[0019] Figure 2 Shows a printed circuit diagram according to Comparative Example 1 of the present invention;

[0020] Figure 3 Shows a printed circuit diagram according to Comparative Example 2 of the present invention;

[0021] Figure 4 Shows a printed circuit diagram according to Comparative Example 5 of the present invention;

[0022] Figure 5A printed circuit diagram of Comparative Example 6 according to the present invention is shown. DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0024] Unless otherwise specified, "room temperature" in the present invention refers to 20-30°C.

[0025] As described in the background of the present invention, the prior art has problems such as low thixotropic index of high elastic resin, poor conformality, printing aspect ratio <0.1, large fluctuation of long-term printing line width, etc., which makes it difficult to meet the needs of precision printing in specific areas. In order to solve the above problems, in a typical embodiment of the present invention, a 3D printing adhesive is provided, the raw materials include UV glue and polyamide wax, the thixotropic index of the 3D printing adhesive is 2 to 2.6, the Young's modulus is ≤10MPa, and the elongation at break is 150 to 350%; the printing line width of the 3D printing adhesive is ≤500μm, the line width fluctuation of 30 lines printed in 80cm is ≤±5%, and the printing aspect ratio is 0.1 to 0.13.

[0026] There are four major categories of thixotropic additives that are most widely used, including fumed silica, organic bentonite, hydrogenated castor oil, and polyamide wax. However, the inventor unexpectedly found during the research that the use of inorganic thixotropic additive fumed silica can improve the thixotropy of the resin material, but at the same time it will increase the hardness of the material and reduce the elasticity and flexibility of the material; among organic thixotropic additives, organic bentonite is prone to accumulation and agglomeration due to its lamellar structure, which is not conducive to the stability of the material during 3D printing and is easy to block the needle; castor oil and its derivatives are generally only suitable for low-polarity systems due to their low polarity, while the main formula of UV glue has a relatively large polarity, and the dispersion effect with castor oil and its derivatives is poor, which is also not conducive to the stable discharge of 3D printing; polyamide wax has better thixotropy and thickening effects, and at the same time has good dispersion stability and is not easy to agglomerate. When it is added as a thixotropic additive, it has a relatively low impact on the elasticity and flexibility of the resin. Therefore, in general, polyamide wax is more suitable for UV elastic glue system.

[0027] At the same time, the inventors unexpectedly discovered during the research process that the existing polyamide wax dispersion process often has the following problems: 1) The polyamide wax is not fully activated and the polyamide wax particles are severely agglomerated in the glue, which makes it easy to clog the needle during the actual printing process and the discharge flow is unstable; 2) The polyamide wax has a poor thixotropic effect on the glue in the UV elastic glue system, resulting in no obvious change in the Young's modulus and elongation at break of the UV elastic glue after polyamide wax activation treatment, and the printed aspect ratio still cannot reach above 0.1, making it unsuitable for some special scenarios of precision printing.

[0028] Based on this, the present invention adds polyamide wax as a thixotropic additive and preferably uses a special dispersion process, which can improve the thixotropy while retaining the high elastic characteristics of the UV elastic glue, and can prevent desorption or deformation caused by different internal stresses during the bending process; and the thixotropic index is controlled to be 2-2.6 to ensure that the 3D printing rubber has a high thixotropic performance, and at the same time, the Young's modulus is limited to ≤10MPa, and the elongation at break is between 150 and 350% to ensure that the 3D printing rubber has a high elastic performance, so as to obtain a high thixotropic and high elastic resin; further control the printing line width to ≤500μm, and the line width fluctuation of 30 lines printed in 80cm is ≤±5%, so as to ensure that the 3D printing rubber has good printing accuracy and long-term printing stability, and limit the printing aspect ratio to 0.1-0.13, which meets the requirements of aspect ratio, low line width, stable printing, etc., and the risk of needle blocking of the rubber is small when used for 3D printing, and the line type uniformity is good. When the 3D printing adhesive of the present invention is applied to flexible display, the thickness and size uniformity of the printed adhesive layer can be precisely controlled, glue overflow and glue creeping can be prevented, and desorption or deformation due to different internal stresses during the bending process can be avoided, so it is suitable for precision printing.

[0029] In a preferred embodiment, the UV glue comprises a main resin, and the main resin comprises one or more of polyurethane acrylate, polyester acrylate, polyether acrylate, silicone modified acrylate and acrylic resin; and / or the particle size D of the polyamide wax max ≤20μm. The above UV glue has higher elasticity, the above polyamide wax has a more suitable particle size, the wax powder particles can be fully unfolded, and the activation effect is better, so as to better meet the requirements of high aspect ratio, low line width, stable discharge and printing.

[0030] Specifically, in a preferred embodiment, the UV glue is one or more of Henkel Loctite's 3318LV, 3410, Permabond's UV 639, Shin-Etsu's KUV-3433-UV, preferably Henkel Loctite's 3318LV; and / or the polyamide wax is one or more of Arkema's LV, SL, SLX, SLT, Super, Optima (France), Core Chemical's D680 (Shanghai), and Metxon's MT Plus (Taiyuan), preferably Arkema's LV (France).

[0031] In order to make it more conducive to making the polyamide wax retain the high elasticity of the UV glue while further improving the thixotropy of the material, in a preferred embodiment, the weight ratio of the UV glue to the polyamide wax is 100:(1-2). Under the above conditions, the 3D printing glue is less likely to block the needle and the printing line uniformity is better.

[0032] In another typical embodiment of the present invention, a method for preparing the above-mentioned 3D printing glue of the present invention is also provided, comprising the following steps: step S1, mixing UV glue and polyamide wax, performing a first fluid shearing, and obtaining a pre-dispersed material; step S2, performing a first mechanical dispersion and a second fluid shearing on the pre-dispersed material in sequence to obtain a pre-treated material; step S3, performing a second mechanical dispersion on the pre-treated material at 60-80°C, the second mechanical dispersion comprising 2-3 dispersion cycles, and performing at least one third fluid shearing between each dispersion cycle to obtain an activated material; step S4, filtering the activated material and performing a fourth fluid shearing, then performing a third mechanical dispersion at 60-80°C, and finally performing a fifth fluid shearing and centrifugation in sequence to obtain a 3D printing glue.

[0033] When polyamide wax is used, it is generally necessary to activate it, and the activation process is essentially the process of changing the state of polyamide wax powder particles into a fibrous interactive network structure, which requires a certain shear force and temperature. The conventional equipment is a high-speed disperser, which provides a large dispersing force and temperature through high-speed rotation to disperse and mix the materials evenly. However, the inventor unexpectedly found in the research process that when using a high-speed disperser to mix or disperse materials, during the gradual activation of polyamide wax powder, the system as a whole is gel-like, and there are dead corners when using a high-speed stirrer, such as the wall and other corner areas cannot form flow, resulting in a large part of the polyamide wax powder not being dissolved in the resin colloid, and there are small particles or agglomerates of polyamide wax. Due to the presence of agglomerates and small particles in the 3D printing adhesive obtained under the above conditions, on the one hand, the risk of needle blocking during printing is greatly increased, and on the other hand, it will also affect the uniformity of the printing line type, which does not meet the actual application requirements of precision printing.

[0034] Moreover, the inventors found in the research process through the investigation of shearing equipment and combined with the actual use that the dispersion force of fluid shearing is relatively small, and the limit particle size is large (greater than 100nm), but overall uniform dispersion can be achieved; while the dispersion force in the mechanical dispersion process is relatively large, and the limit particle size can be very small, but there will be dead corners in the actual use of high-viscosity fluid systems. The present invention combines the advantages of both to improve the dispersion process. Specifically, the present invention first mixes the UV glue with the polyamide wax, performs the first fluid shearing, transmits the shear force through the fluid medium (UV glue) and acts on the polyamide wax particles, pre-disperses them, improves the dispersion state and uniformity of the polyamide wax in the UV glue colloid, and obtains a pre-dispersed material.

[0035] Subsequently, the pre-dispersed material is subjected to the first mechanical dispersion and the second fluid shearing in sequence. The strong shearing force of the mechanical dispersion is first used to further break up the polyamide wax powder and improve the agglomeration of the powder particles. Through the combination of mechanical dispersion and fluid shearing, the polyamide wax in the system is in a slightly dissolved state, which increases the dispersion density of the polyamide wax in the UV glue, which is beneficial to improving the subsequent printing line stability and obtaining the pre-treated material.

[0036] Then the pre-treated material is subjected to a second mechanical dispersion at 60-80°C. By applying mechanical force to the dispersed system under heating conditions, the physical and chemical properties of the substances in the system are changed, and a series of chemical reactions are accompanied to achieve the purpose of dispersion. This temperature is the activation temperature of polyamide wax. The polyamide wax powder particles are dispersed by heat, softened and expanded, and the polyamide molecular chains are stretched out under the action of shear force. When there is no external shear force or the temperature is reduced, the polyamide molecules dispersed in the entire system form in situ intermolecular hydrogen bonds, forming a fibrous, interactive network structure, and providing thixotropy. When the system is subjected to external shear force, the intermolecular hydrogen bonds are destroyed, the network structure is destroyed, and the overall viscosity decreases; when the shear force disappears, the hydrogen bonds are re-formed, the cross-linked network structure is restored, and the system viscosity gradually recovers over time. The second mechanical dispersion includes 2-3 dispersion cycles, and at least one third fluid shear is performed between each two dispersion cycles, which can ensure that the polyamide wax powder is activated under the premise of uniform dispersion, reduce the appearance of polyamide wax agglomerates, and obtain activated materials.

[0037] Finally, the activated material is filtered to remove a very small amount of possible small particles or agglomerates of polyamide wax, and the fourth fluid shear is performed, and then the third mechanical dispersion is performed at 60-80°C to reduce the damage to the overall network structure of the material due to filtration. At the same time, a small amount of polyamide wax agglomerates that have not been activated in the activation process are supplemented with activation to avoid the presence of incompletely activated polyamide wax agglomerates in the rubber, resulting in defects such as holes and protrusions, which in turn make the line shape uneven. Finally, the fifth fluid shear is performed to ensure the overall uniformity and dispersibility of the slurry. Finally, centrifugal degassing is performed to obtain the 3D printing rubber to prevent breakpoints or even material breakage during the printing process due to the presence of bubbles.

[0038] The present invention can avoid the agglomeration of polyamide wax in 3D printing sizing material by improving the sizing material dispersion process, and reduce the undispersed powder by making the polyamide wax fully dispersed in the UV glue, reduce the risk of needle blocking, improve the uniformity of printing line type, and further prevent the occurrence of overflow and creeping glue from the source, and realize the precise control of the thickness and uniformity of the printing glue layer, and obtain a thixotropic index of 2 to 2.6, a Young's modulus of ≤10MPa, an elongation at break of 150 to 350%, a printing line width of ≤500μm, a line width fluctuation of ≤±5% for 80cm printing 30 lines, and a printing aspect ratio of 0.1 to 0.133D printing sizing material, which meets the precision printing requirements of large aspect ratio, low line width, and low line width fluctuation, and has broad application prospects. The present invention can improve the dispersibility problem of polyamide wax, prevent the risk of needle blocking and improve the uniformity of line type through the design and optimization of the preparation process, and finally obtain a 3D printing sizing material that meets the requirements of precision printing in a specific area. The preparation method is simple and easy to operate, wherein the equipment used for fluid shearing and mechanical dispersion can be conventional equipment in the art, such as fluid shearing can be performed in a slurry mixer, and mechanical dispersion can be performed in a magnetic heating stirrer. In a preferred embodiment, in step S1, the temperature of the first fluid shear is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min. Under the above conditions, the dispersion state and uniformity of polyamide wax in UV glue colloid can be better improved, which is conducive to achieving precision printing.

[0039] In order to cause the polyamide wax powder to enter a slightly dissolved state, thereby further improving the activation effect by improving the dispersion uniformity, in a preferred embodiment, in step S2, the temperature of the first mechanical dispersion is 30-50°C, the rotation speed is 1000-3000rpm, and the time is 0.5-3h; and / or the temperature of the second fluid shear is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min.

[0040] In a preferred embodiment, in step S3, the temperature of the second mechanical dispersion is 60-80°C, the rotation speed is 1000-3000rpm, and the total time is 0.5-1h; and / or the time of a single dispersion cycle is 15-25min; and / or the temperature of the third fluid shear is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min. Under the above conditions, the polyamide wax powder can be fully and evenly activated, and the generation of agglomerates can be reduced, thereby better avoiding defects such as needle blocking and uneven linear shape in the rubber during 3D printing.

[0041] In order to make the polyamide wax powder in the system more fully activated and further reduce the linear defects caused by unactivated powder particles, in a preferred embodiment, in step S4, the temperature of the fourth fluid shear is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min; and / or the temperature of the third mechanical dispersion is 60-80°C, the rotation speed is 1000-3000rpm, and the time is 10-30min; and / or the temperature of the fifth fluid shear is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min.

[0042] The present invention first performs low-temperature and long-term mechanical dispersion, so that the polyamide wax powder first presents a uniform slightly dissolved state; then performs high-temperature and short-time mechanical dispersion, so that the polyamide wax powder is fully activated and agglomerates are reduced; finally, high-temperature and rapid mechanical dispersion is performed to reduce the damage to the overall network structure of the material due to filtration, and at the same time, a small amount of polyamide wax agglomerates that are not activated in the activation process are supplementarily activated, thereby achieving the best dispersion effect and better avoiding needle blockage during 3D printing.

[0043] In order to further remove the polyamide wax powder particles that may remain in the previous step, thereby further improving the subsequent printing stability, in a preferred embodiment, in step S4, a filter screen is used for filtering, and the pore size of the filter screen is 5-50 μm; and / or the centrifugal temperature is 20-30°C, the rotation speed is 2000-4000rpm, and the time is 5-10min; and / or after the fifth fluid shear, step S4 also includes the following steps: rolling the material, shearing the sixth fluid and centrifuging it in turn to obtain a 3D printing rubber material; wherein, a three-roller machine is used for rolling, and the rolling gap of the three-roller machine is 80-40μm\40-20μm\20-10μm\10-5μm, further improving the dispersibility of the polyamide wax powder; and / or the sixth fluid shear temperature is 20-30°C, the rotation speed is 1500-2000rpm, and the time is 5-20min, so that the material is more fully mixed and evenly dispersed, thereby reducing the breakpoints or material breakages that occur during the printing process, and further improving the linear uniformity.

[0044] In another typical embodiment of the present invention, there is also provided the application of the above-mentioned 3D printing adhesive of the present invention in the precise control of printed circuits in flexible display, precision optics and electronic circuit protection. For example, it is used for a flexible screen, and the flexible screen includes a substrate, a metal circuit and a protective layer. The material of the substrate includes a flexible polymer, and the protective layer is prepared by 3D printing and photocuring in sequence using the above-mentioned 3D printing adhesive of the present invention. The adhesive layer formed by the 3D printing adhesive of the present invention is applied to a flexible display, and the thickness and uniformity of the adhesive layer can be precisely controlled to avoid the occurrence of glue overflow, glue creeping, bending desorption or bending deformation. It can be used as a protective layer for metal circuits in a flexible screen, and the resistance and durability of the flexible substrate (soft board) are increased, thereby reducing the risk of bright lines and abnormal display of flexible screen products during the bending process and subsequent use.

[0045] Typically but not limitatively, the weight ratio of UV glue to polyamide wax is 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9, 100:2 or a range consisting of any two of them.

[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0047] Example 1

[0048] (1) Pre-dispersion: Add 1.5 parts of thixotropic additive polyamide wax (particle size D max <20μm, LV from Arkema of France) and 100 parts of UV glue (Hengkel Loctite 3318LV, the main resin is polyurethane acrylate and acrylic resin); use a mixer to mix at 1500rpm for 10min at room temperature to perform the first fluid shearing to obtain a pre-dispersed material.

[0049] (2) Pretreatment: Place a magnetic bar in a mixing tank, place the mixing tank in a water bath, control the water bath temperature at 40°C, stir at 1000 rpm for 3 hours, perform a first mechanical dispersion, and use a slurry mixer to mix at 1500 rpm for 10 minutes at room temperature to perform a second fluid shear to obtain a pretreated material.

[0050] (3) Activation: The water bath temperature was raised to 70°C and stirred at 1000 rpm for 1 hour to perform a second mechanical dispersion. Every 20 minutes, a mixer was used to mix at 1500 rpm for 5 minutes at room temperature to perform a third fluid shearing to obtain an activated material.

[0051] (4) Post-treatment: After filtering the activated material with a 5 μm filter, mix it with a mixer at 1500 rpm for 5 minutes at room temperature to perform the fourth fluid shearing, then put the mixing tank into a 70°C water bath and stir it at 1000 rpm for 20 minutes to perform the third mechanical dispersion, mix it with a mixer at 1500 rpm for 5 minutes at room temperature to perform the fifth fluid shearing, grind it with a three-roll mill (80-40 μm / 40-20 μm / 20-10 μm / 10-5 μm), mix it with a mixer at 1500 rpm for 5 minutes at room temperature to perform the sixth fluid shearing, take it out and put it into a tube, and centrifuge it at 2000 rpm for degassing at room temperature for 10 minutes to obtain a 3D printing rubber material.

[0052] Example 2

[0053] The difference from Example 1 is that: (1) Pre-dispersion: 1 part of thixotropic additive polyamide wax (particle size D max <20μm, LV from Arkema, France) and 100 parts of UV glue (Henkel Loctite 3318LV); mixed with a mixer at 1500rpm for 20min at room temperature to perform the first fluid shearing to obtain a pre-dispersed material.

[0054] Example 3

[0055] The difference from Example 1 is that: (1) Pre-dispersion: 2 parts of thixotropic additive polyamide wax (particle size D max <20μm, LV from Arkema, France) and 100 parts of UV glue (Henkel Loctite 3318LV); mixed with a mixer at 2000rpm for 5min at room temperature to perform the first fluid shearing to obtain a pre-dispersed material.

[0056] Example 4

[0057] The difference from Example 1 is that (2) pretreatment: a magnetic bar is placed in a mixing tank, the mixing tank is placed in a water bath, the water bath temperature is controlled at 30°C, and the mixture is stirred at 1000 rpm for 3 hours to perform a first mechanical dispersion, and a slurry mixer is used to mix the mixture at 1500 rpm for 20 minutes at room temperature to perform a second fluid shearing to obtain a pretreated material.

[0058] Example 5

[0059] The difference from Example 1 is that (2) pretreatment: a magnetic bar is placed in a mixing tank, the mixing tank is placed in a water bath, the water bath temperature is controlled at 50°C, and the mixture is stirred at 3000 rpm for 0.5 h to perform a first mechanical dispersion, and a slurry mixer is used to mix the mixture at 2000 rpm for 5 min at room temperature to perform a second fluid shearing to obtain a pretreated material.

[0060] Example 6

[0061] The difference from Example 1 is that (3) activation: the water bath temperature is raised to 60°C, and the mixture is stirred at 1000 rpm for 1 hour to perform a second mechanical dispersion, and a mixer is used to mix the mixture at 1500 rpm for 20 minutes at room temperature every 20 minutes to perform a third fluid shearing to obtain an activated material.

[0062] Example 7

[0063] The difference from Example 1 is that (3) activation: the water bath temperature is raised to 80°C, and the mixture is stirred at 3000 rpm for 0.5 h to perform a second mechanical dispersion, and a mixer is used to mix the mixture at 2000 rpm for 5 min at room temperature every 15 min to perform a third fluid shearing to obtain an activated material.

[0064] Example 8

[0065] The difference from Example 1 is that (4) post-treatment: after filtering the activated material with a 25 μm filter screen, mix it with a slurry mixer at 1500 rpm for 20 minutes at room temperature to perform the fourth fluid shearing, then put the mixing tank into a 60°C water bath and stir it at 1000 rpm for 30 minutes to perform the third mechanical dispersion, mix it with a slurry mixer at 1500 rpm for 20 minutes at room temperature to perform the fifth fluid shearing, use a three-roll mill (80-40 μm / 40-20 μm / 20-10 μm / 10-5 μm) for grinding, and mix it with a slurry mixer at 1500 rpm for 20 minutes at room temperature to perform the sixth fluid shearing, take it out and put it into a tube, and centrifuge it at 2000 rpm for degassing for 5 minutes at room temperature to obtain a 3D printing rubber material.

[0066] Example 9

[0067] The difference from Example 1 is that (4) post-treatment: after filtering the activated material with a 50 μm filter screen, mix it with a slurry mixer at 2000 rpm for 5 minutes at room temperature to perform the fourth fluid shearing, then put the mixing tank into an 80°C water bath and stir it at 3000 rpm for 10 minutes to perform the third mechanical dispersion, mix it with a slurry mixer at 2000 rpm for 5 minutes at room temperature to perform the fifth fluid shearing, grind it with a three-roll mill (80-40 μm / 40-20 μm / 20-10 μm / 10-5 μm), mix it with a slurry mixer at 2000 rpm for 5 minutes at room temperature to perform the sixth fluid shearing, take it out and put it into a tube, and degas it by centrifugation at 4000 rpm at room temperature for 10 minutes to obtain a 3D printing rubber material.

[0068] Example 10

[0069] The difference from Example 1 is that: (1) Pre-dispersion: 1.5 parts of thixotropic additive polyamide wax (particle size Dmax <20μm, Shanghai Core Chemical D680) and 100 parts of UV glue (Shin-Etsu KUV-3433-UV, the main resin is siloxane-modified acrylic resin); use a mixer to mix at 1500rpm for 10min at room temperature to perform the first fluid shearing to obtain a pre-dispersed material.

[0070] Comparative Example 1 (High-speed disperser)

[0071] (1) Pre-dispersion: Add 1.5 parts of thixotropic additive polyamide wax (particle size D max <20μm, LV from Arkema of France) and 100 parts of UV glue (Loctite 3318LV from Henkel) were mixed with a mixer at 1500 rpm for 10 min at room temperature to uniformly mix the two.

[0072] (2) Activation: The material is dispersed in a high-speed disperser at 10,000 rpm for 30 min, and the temperature generated by high-speed dispersion (about 70° C.) is used to activate the polyamide wax molecules.

[0073] (3) Post-treatment: The activated material was mixed with a mixer at 1500 rpm for 5 min at room temperature, then taken out and put into a tube, and centrifuged and degassed at 2000 rpm for 10 min at room temperature to obtain a 3D printing rubber material.

[0074] Comparative Example 2 (SiO 2 )

[0075] (1) Dispersion: Add 1.5 parts of thixotropic additive SiO into the mixing tank. 2 (Hydrophobic gas phase SiO 2 , Germany Wacker H15) and 100 parts of UV glue (Henkel Loctite 3318LV) were mixed with a mixer at 1500 rpm for 10 minutes at room temperature to uniformly mix the two.

[0076] (2) Post-treatment: The material was mixed with a mixer at 1500 rpm for 5 min at room temperature, then taken out and put into a tube, and centrifuged and degassed at 2000 rpm for 10 min at room temperature to obtain a 3D printing rubber material.

[0077] Comparative Example 3 (organic bentonite)

[0078] (1) Pre-dispersion: Add 1.5 parts of thixotropic agent organic bentonite (BYK7303, BYK Chemical, Germany) and 100 parts of UV glue (Loctite 3318LV, Henkel) into a mixing tank and mix them evenly at room temperature at 1500 rpm for 10 min using a mixer.

[0079] (2) Activation: Place the mixing tank in a water bath, control the water bath temperature at 60°C, and stir at 1000 rpm for 1 h.

[0080] (3) Post-treatment: The activated material was mixed with a mixer at 1500 rpm for 5 min at room temperature, then taken out and put into a tube, and centrifuged and degassed at 2000 rpm for 10 min at room temperature to obtain a 3D printing rubber material.

[0081] Comparative Example 4 (Hydrogenated Castor Oil)

[0082] (1) Pre-dispersion: Add 1.5 parts of thixotropic agent hydrogenated castor oil (castor oil modified derivative, Hemmings ST) and 100 parts of UV glue (Henkel Loctite 3318LV) into a mixing tank, and mix them evenly at room temperature at 1500 rpm for 10 minutes using a mixer.

[0083] (2) Activation: Place the mixing tank in a water bath, control the water bath temperature at 55°C, and stir at 1000 rpm for 1 h.

[0084] (3) Post-treatment: The activated material was mixed with a mixer at 1500 rpm for 5 min at room temperature, then taken out and put into a tube, and centrifuged and degassed at 2000 rpm for 10 min at room temperature to obtain a 3D printing rubber material.

[0085] Comparative Example 5

[0086] The difference from Example 1 is that the pre-treatment in step (2) is not performed.

[0087] Comparative Example 6

[0088] The difference from Example 1 is that the post-treatment in step (4) is not performed.

[0089] The mechanical properties of the 3D printing adhesives prepared in the above examples and comparative examples were tested, and the results are shown in Tables 1 and 2.

[0090] The 3D printing adhesives prepared in the above examples and comparative examples were printed on a machine, and the performance was recorded. The results are shown in Tables 1 and 2. The printing circuit diagram of Example 1 is shown in Figure 1 As shown; the printed circuit diagram of comparative example 1 is as shown Figure 2 As shown; the printed circuit diagram of Comparative Example 2 is as shown Figure 3 As shown; the printed circuit diagram of Comparative Example 5 is as shown Figure 4 As shown; the printed circuit diagram of Comparative Example 6 is as shown Figure 5 It can be seen that compared with the comparative example, the 3D printing adhesive of the embodiment of the present invention has good line uniformity and good shape retention performance, meets the requirements of high aspect ratio, low line width and stable printing, and is suitable for precision printing.

[0091] Test method:

[0092] Needle discharge condition, line shape, and precipitation phenomenon: visual observation.

[0093] Line width and line width fluctuation: calculated after being photographed and measured using an ultra-depth-of-field microscope;

[0094] Aspect ratio: step profiler;

[0095] Viscosity: AMETEK BROOKFIELD DVNext, 52#, 100rpm@25℃;

[0096] Thixotropic index: η(10rpm) / η(100rpm);

[0097] Curing hardness: GB / T 2411-2008, Shore A;

[0098] Adhesion: GB / T 9286-2021, 100-grid test (PET film);

[0099] Tensile strength: GB / T 528-2009, electronic universal material testing machine;

[0100] Glass transition temperature Tg: GB / T 19466.1-2004, DSC;

[0101] Young's modulus: GB / T 33061.1-2016, DMA850 dynamic mechanical analyzer;

[0102] Elongation at break: GB / T 228-2002, universal testing machine.

[0103] Table 1

[0104]

[0105]

[0106] Table 2

[0107]

[0108] Among them, printing line type OK means that there are no undesirable conditions such as line breakage and line distortion during the printing process, or the probability of the above undesirable conditions occurring is less than 5%, and printing line type NG means that the OK condition cannot be met.

[0109] As can be seen from the above, compared with the comparative example, each embodiment of the present invention improves the conformal performance of the 3D printing rubber by adding polyamide wax as a thixotropic additive, and controls the thixotropic index, printing line width fluctuation and other parameters within a specific range to meet the requirements of precision printing in a specific area, and can improve the thixotropy while retaining the high elasticity of the resin, meet the requirements of high aspect ratio, low line width, and stable printing, and has a low risk of needle blocking when used for 3D printing, good line uniformity, and is suitable for precision printing. And through the design and optimization of the preparation process, the dispersibility problem of polyamide wax can be improved, the risk of needle blocking can be prevented, and the line uniformity can be improved, and finally a 3D printing rubber that meets the requirements of precision printing in a specific area can be obtained.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A 3D printing adhesive, characterized in that: The raw materials include UV glue and polyamide wax. The 3D printing rubber has a thixotropic index of 2 to 2.6, a Young's modulus of ≤10 MPa, and an elongation at break of 150 to 350%; The printing line width of the 3D printing adhesive is ≤500 μm, the line width fluctuation of 30 lines printed in 80 cm is ≤±5%, and the printing aspect ratio is 0.1-0.

13.

2. The 3D printing adhesive according to claim 1, characterized in that: The UV glue comprises a main resin, and the main resin comprises one or more of polyurethane acrylate, polyester acrylate, polyether acrylate, silicone-modified acrylate and acrylic resin; and / or The particle size D of the polyamide wax max ≤20μm.

3. The 3D printing adhesive according to claim 1 or 2, characterized in that: The UV adhesive is one or more of Henkel Loctite's 3318LV, 3410, Permabond's UV 639, Shin-Etsu's KUV-3433-UV; and / or The polyamide wax is one or more of LV, SL, SLX, SLT, Super, Optima of Arkema, D680 of Core Chemical, and MT Plus of Metson.

4. The 3D printing adhesive according to claim 1 or 2, characterized in that: The weight ratio of the UV glue to the polyamide wax is 100:(1-2).

5. The method for preparing the 3D printing adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, mixing UV glue and polyamide wax, and performing first fluid shearing to obtain a pre-dispersed material; Step S2, sequentially subjecting the pre-dispersed material to a first mechanical dispersion and a second fluid shearing to obtain a pre-treated material; Step S3, subjecting the pre-treated material to a second mechanical dispersion at 60-80° C., wherein the second mechanical dispersion includes 2-3 dispersion cycles, and at least one third fluid shearing is performed between each dispersion cycle to obtain an activated material; Step S4, filtering the activated material and performing a fourth fluid shearing, then performing a third mechanical dispersion at 60-80° C., and finally performing a fifth fluid shearing and centrifugation in sequence to obtain the 3D printing glue.

6. The preparation method according to claim 5, characterized in that: In the step S1, The shearing temperature of the first fluid is 20-30° C., the rotation speed is 1500-2000 rpm, and the time is 5-20 min.

7. The preparation method according to claim 5, characterized in that: In the step S2, The temperature of the first mechanical dispersion is 30-50° C., the rotation speed is 1000-3000 rpm, and the time is 0.5-3 h; and / or The second fluid is sheared at a temperature of 20 to 30° C., a rotation speed of 1500 to 2000 rpm, and a time of 5 to 20 minutes.

8. The preparation method according to claim 5, characterized in that: In the step S3, The temperature of the second mechanical dispersion is 60-80° C., the rotation speed is 1000-3000 rpm, and the total time is 0.5-1 h; and / or The time of a single dispersion cycle is 15 to 25 minutes; and / or The shearing temperature of the third fluid is 20-30° C., the rotation speed is 1500-2000 rpm, and the time is 5-20 min.

9. The preparation method according to claim 5, characterized in that: In the step S4, The fourth fluid is sheared at a temperature of 20 to 30° C., a rotation speed of 1500 to 2000 rpm, and a time of 5 to 20 min; and / or The temperature of the third mechanical dispersion is 60-80°C, the rotation speed is 1000-3000rpm, and the time is 10-30min; and / or The fifth fluid is sheared at a temperature of 20 to 30° C., a rotation speed of 1500 to 2000 rpm, and a time of 5 to 20 minutes.

10. The preparation method according to claim 5, characterized in that: In the step S4, The filtering is performed using a filter, wherein the pore size of the filter is 5 to 50 μm; and / or The centrifugation temperature is 20-30°C, the rotation speed is 2000-4000 rpm, and the time is 5-10 min; and / or After the fifth fluid shearing, the step S4 further includes the following steps: rolling the material, shearing with the sixth fluid and centrifuging in sequence to obtain the 3D printing glue; wherein the temperature of the sixth fluid shearing is 20-30° C., the rotation speed is 1500-2000 rpm, and the time is 5-20 min.

11. Application of the 3D printing adhesive according to any one of claims 1 to 4 in precise control of printed circuits in flexible displays, precision optics and electronic circuit protection.

Citation Information

Patent Citations

  • UV curing cofferdam glue and preparation method thereof

    CN115537167A